MENINGKATKAN HASIL BELAJAR MENGGUNAKAN STRATEGI PETA KONSEP PADA MATERI HIDROKARBON SISWA KELAS X-1 SMA NEGERI 10 BANJARMASIN - Adriana, Nita; Leny, Leny; Iriani, Rilia (Vidya Karya Jurnal Kependidikan, 2014)
Research on improving student learning outcomes using concept mapping Â strategy Â on Â hydrocarbon Â material Â in Â class Â X-1 Â SMAN Â 10 Banjarmasin has been implemented. This Â research Â aims Â to (1) know Â teacherâs and studentsâ activities, (2) improve learning outcomes (3) study students response to concept mapping strategy on hydrocarbon material. This research used classroom action research design, with 2 cycles. Subjects of this research were students of class X-1 in SMAN 10 Banjarmasin. Data were obtained from assessment of teacher activity, student activity, cognitive tests and questionnaire Â responses. The results showed that the use of map concept strategy increased: (1) teacher activities, from good criteria in the first cycle to very good criteria in the second cycle, (2) studentsâ activities from good criteria in the first cycle to Â very good criteria Â in Â the Â second Â cycle, Â (3) students outcomes increased fromÂ  Â 63.28% in the first cycle to 81.21% in the second cycle; (4) Learning using Â map concept received a positive response from the students.